Probiotics in Health and Disease in Children - Naqvi, Shehla H.; Ali, S. Inkisar; Sohail, Fadieleh (Infectious Diseases Journal of Pakistan, 2023)
Probiotics are living microorganisms which are being used in the management of multiple medical conditions associated with disturbance of normal microflora of human mucosa. The expected benefits and potential risks of probiotics use have been evaluated and guidelines have been suggested for their safe and effective use in hospitalized and ambulatory pediatric patients. If minimal benefit is expected then financial cost should also be taken into account. Research is going on to develop probiotics by isolating the beneficial component of the microbe, and thus decrease the potential risks of using live microorganisms.